2014
DOI: 10.1063/1.4884336
|View full text |Cite
|
Sign up to set email alerts
|

In-situ neutron diffraction of LaCoO3 perovskite under uniaxial compression. II. Elastic properties

Abstract: Articles you may be interested inIn-situ neutron diffraction of LaCoO3 perovskite under uniaxial compression. I. Crystal structure analysis and texture developmentCalculations of elastic constants and development of elastic anisotropy under uniaxial compression in originally isotropic polycrystalline LaCoO 3 perovskite are reported. The lattice strains in individual (hkl) planes as well as average lattice strain were determined both for planes oriented perpendicular and parallel to the loading direction using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…One of the possible explanations for the increase of effective Young's modulus of pure LaCoO 3 could be connected to the strong elastic anisotropy of this compound. As it was established in [10], a strong texture formed during the loading of this perovskite at room temperature, when the volume of the domains with a higher elastic modulus along loading direction increased thus leading to an increase in observed effective Young's modulus. Increase in temperature could bring about a significant increase in the mobility of the domain walls and, therefore, formation of texture might easily be facilitated, resulting in an increase in the effective Young's modulus at much lower applied stress, such as for example 8 MPa as it was applied in the current study.…”
Section: Stressmentioning
confidence: 54%
See 1 more Smart Citation
“…One of the possible explanations for the increase of effective Young's modulus of pure LaCoO 3 could be connected to the strong elastic anisotropy of this compound. As it was established in [10], a strong texture formed during the loading of this perovskite at room temperature, when the volume of the domains with a higher elastic modulus along loading direction increased thus leading to an increase in observed effective Young's modulus. Increase in temperature could bring about a significant increase in the mobility of the domain walls and, therefore, formation of texture might easily be facilitated, resulting in an increase in the effective Young's modulus at much lower applied stress, such as for example 8 MPa as it was applied in the current study.…”
Section: Stressmentioning
confidence: 54%
“…It was reported that polycrystalline LaCoO 3 based perovskites exhibit nonlinear ferroelastic behavior, which can be well explained by the kinetics of ferroelastic switching and corresponding changes in the cobaltite's microstructure and crystallographic orientation during loading [9]. The phenomena of domain switching and texture development were reported to be responsible for the appearance of elastic anisotropy and stressstrain hysteresis during deformation [9,10]. It was also reported that at room temperature both pure LaCoO 3 and Ca doped LaCoO 3 have R3 c low symmetry rhombohedral structure with a =5.378 Å and  =60.8 o for pure LaCoO 3 , and a =5.374 Å and  =60.72 o for 20% Ca doped LaCoO 3 , which is in perfect agreement with previously reported measurements [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The high resolution synchrotron diffraction study of domain switching and texture formation in La 0.8 Ca 0.2 CoO 3 perovskite under in situ compressive loading was performed. 16 A similar study of pure LaCoO 3 perovskite ceramic was reported, [17][18][19] where it was established that during loading the texture was formed leading to elastic anisotropy in the material. As the texture is inevitably connected to the growth of domains with preferred crystallographic orientation and the corresponding increase in the volume fraction of certain domains, it is possible to estimate the anisotropy and elastic properties of LaCoO 3 in different crystallographic directions if the relevant elastic properties are known.…”
Section: Introductionmentioning
confidence: 65%
“…This can be understood in terms of Young's modulus of bulk STO (YSTO ~ 273 GPa), [36] which is much larger than that of bulk LCO (YLCO ~ 150 GPa). [38][39][40] Therefore, a larger lattice deformation is expected for the LCO film bulk, while the response of the LCO interface layers to pressure is partially constrained by clamping with the STO substrate/capping layer.…”
Section: Previous Work On Bulk Lco Demonstrated That the Lattice Volumentioning
confidence: 99%